AGE AND GROWTH OF THE JUVENILES OF KOTH OTOLITHOIDES BRUNNEUS (DAY) IN BOMBAY WATERS - Jayaprakash, A A (Indian Journal of Fisheries, 2011)
Otolithoides brunneus (Day), locally called 'Koth', occurring along theBombay and Saurashtra waters, is a sciaenid, growing to a size of over 160cm and supporting a fishery of some importance (Jayaraman et al 1959, Bhattet al 1967, Rao et al 1966, 1972). Karandikar and Thakur (1951) studiedthe anatomy of 'Koth'. Kutty (1961, 1967) studied the age and growth ofthis species by using the scales and otoliths. He also made a brief report oncertain other aspects of its biology